3D printing low-carbon concrete containing modified recycled aggregate and micro-powder enhancer
Through the combination of modified regenerated aggregate and micropowder reinforcement, the problems of reduced strength caused by high porosity of regenerated concrete aggregates and inability to recycle waste slurry are solved, and the mechanical strength and fluidity of 3D printed concrete are improved, as well as Reduced carbon emissions and resource waste.
Patent Information
- Application Number
- CN202411511675.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-28
AI Technical Summary
Among the existing 3D printed concrete materials, the porosity of recycled concrete aggregates is high, resulting in increased water absorption and reduced strength, affecting the fluidity and structural strength of 3D printed concrete. At the same time, the waste slurry generated during the production process of commercial mixing stations Unable to be recycled, resulting in carbon emissions and waste of resources.
Modified regenerated aggregate and micro-powder reinforcement are used to form modified regenerated aggregate by placing the regenerated concrete coarse aggregate in sodium or potassium water glass for ultrasonic treatment and carbon dioxide carbonization; at the same time, silicate cement-based waste is used. The slurry is prepared as a modified regenerated micropowder reinforcement, which is mixed with γ-C2S powder for carbonization to form nanosilica and calcium carbonate fillers, improving the mechanical strength and fluidity of the concrete.
It improves the mechanical strength and fluidity of 3D printed concrete, reduces carbon emissions, realizes the effective utilization of waste slurry, and enhances the density and strength of the concrete structure.
Smart Images

Figure CN119504201A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of 3D printing material preparation, and in particular to a 3D printed low-carbon concrete containing modified recycled aggregate and a micro-powder reinforcer. Background Art
[0002] Concrete is an irreplaceable basic building material. 3D printing concrete is a new construction technology that combines 3D printing technology with traditional concrete materials. It uses a printer controlled by a computer software program to quickly print concrete materials layer by layer into complex structures. Traditional 3D printing concrete materials mainly use cement as the gelling component, but the production of cement not only consumes a lot of energy, but also emits a lot of carbon dioxide.
[0003] Recycled concrete aggregates are obtained from discarded concrete blocks through processes such as crushing, cleaning, and grading. Reusing them in the preparation of concrete materials helps reduce the raw materials required for the preparation of new concrete, thereby reducing carbon emissions. However, the high porosity of recycled concrete aggregates leads to increased water absorption and reduced strength compared to natural aggregates, which in turn leads to insufficient fluidity and strength of the prepared 3D printed concrete, affecting the construction and structural strength of 3D printed concrete. In addition, in the process of producing cement-based slurries at commercial mixing stations, a large amount of waste slurries generated by equipment such as cleaning mixing tanks are also generated. The precipitates are mainly silicate cement-based materials. Since they have undergone hydration reactions and do not have gelling properties, they cannot be recycled as cement. The treatment and utilization of these wastes have become one of the problems faced by commercial mixing stations. Summary of the invention
[0004] The present invention provides a 3D printed low-carbon concrete containing modified recycled aggregate and a micro-powder reinforcer, which not only improves the mechanical strength and fluidity of the 3D printed concrete prepared from the recycled concrete aggregate, but also consumes carbon dioxide and reduces carbon emissions. Specifically, the technical solution of the present invention is as follows.
[0005] A 3D printed low-carbon concrete containing modified recycled aggregate and micro-powder fortifier, the raw material composition of which includes the following components: 300-360 parts by weight of cement cementitious material, 620-750 parts by weight of modified recycled aggregate, 400-480 parts by weight of fine aggregate, 50-70 parts by weight of modified recycled micro-powder fortifier, 4.5-7.2 parts by weight of water reducer, clean water, and a water-cement ratio of 0.35-0.45. The modified recycled aggregate and the modified recycled micro-powder fortifier are prepared by the following method: (1) The recycled concrete coarse aggregate is placed in sodium or potassium water glass and then subjected to ultrasonic treatment. The coarse aggregate is then separated and placed in a closed container with a carbon dioxide atmosphere for carbonization treatment. After completion, the obtained coarse aggregate is heated to obtain pre-treated recycled aggregate.
[0006] (2) The pretreated recycled aggregate is placed in saturated lime water and then subjected to a heating and heat preservation treatment. After completion, the solid matter is separated to obtain the modified recycled aggregate.
[0007] (3) Separate the precipitate from the silicate cement-based waste slurry after settling, dry it and grind it into powder, and 2 The S powder is mixed with water to form a wet material, which is then placed in a sealed container with a carbon dioxide atmosphere for carbonization treatment. After the carbonization treatment is completed, a heating treatment is performed, and the obtained solid matter is ground to obtain the modified regenerated micro-powder strengthener.
[0008] Furthermore, the water reducer includes any one of a polycarboxylate water reducer, a lignin sulfonate water reducer, a naphthalene water reducer, an aliphatic water reducer, and the like.
[0009] Furthermore, the particle size of the fine aggregate is 0.5-1 mm. Optionally, the fine aggregate includes at least one of river sand, machine-made sand, etc.
[0010] Furthermore, in step (1), the amount of recycled concrete coarse aggregate added to the sodium or potassium water glass is 25-70 g / L. Optionally, the mass fraction of the sodium or potassium water glass is not less than 20%.
[0011] Furthermore, in step (1), the ultrasonic treatment time is 30 to 40 minutes. Optionally, the particle size of the recycled concrete coarse aggregate is 10 to 20 mm.
[0012] Furthermore, in step (1), the temperature of the carbonization treatment is 40-60° C., and the time is 1-1.5 h. Optionally, the pressure in the sealed container is 0.2-0.35 MPa.
[0013] Furthermore, in step (1), the heating treatment temperature is 180-250° C., and the heating treatment is performed at this temperature until the weight of the coarse aggregate becomes constant.
[0014] Furthermore, in step (2), the amount of pre-treated recycled aggregate added to the saturated lime water is 20-40 g / L.
[0015] Furthermore, in step (2), the heating temperature is 50-80° C. and the heating time is 4-7 hours.
[0016] Furthermore, in step (3), the powder, γ-C2 The ratio of S powder to water is 1-1.15 parts by weight: 0.18-0.25 parts by weight: 0.3-0.4 parts by weight. 2 The fineness of S powder is not less than 200 mesh.
[0017] Furthermore, in step (3), the carbonization treatment time is 30 to 50 minutes. Optionally, the pressure in the sealed container is 0.2 to 0.35 MPa.
[0018] Furthermore, in step (3), the temperature of the heating treatment is 80-100°C and the time is 1-2 hours. Optionally, the fineness of the modified regenerated micropowder fortifier is 300-600 mesh.
[0019] Compared with the prior art, the present invention has at least the following beneficial technical effects: There are many pores and cracks in the coarse aggregate of recycled concrete, which leads to the deterioration of the fluidity and mechanical strength of the 3D printed concrete prepared therefrom. To this end, the present invention first uses the pores of the coarse aggregate of recycled concrete to absorb sodium or potassium water glass, and then performs carbonization treatment in a carbon dioxide atmosphere, thereby reacting to form carbonate and silicate precipitation. Not only does it achieve the solidification of carbon dioxide, it helps to offset the carbon emissions generated in the production process of the cementitious material. Moreover, the silicate precipitation is decomposed after heating treatment to form nano-silicon dioxide particles that fill the pores and cracks of the coarse aggregate of recycled concrete, reducing the porosity. After the above-mentioned recycled concrete coarse aggregate is placed in saturated lime water for further treatment, on the one hand, the nano-silicon dioxide particles react with the calcium hydroxide in the saturated lime water to form a hydrated calcium silicate gel to further fill, bond and repair the pores and cracks inside the coarse aggregate. On the other hand, the carbonate reacts with the calcium hydroxide in the saturated lime water to form nano-calcium carbonate particles that fill the pores and cracks inside the coarse aggregate, which also reduces the porosity. The 3D printed concrete prepared by the modified recycled aggregate obtained by the above method not only has good fluidity and mechanical strength, but the hydrated calcium silicate and nano calcium carbonate on the surface of the coarse aggregate also have the function of inducing hydration. As the nucleation site for the hydration of cement binder, it can promote the hydration reaction, form more cementitious components, and improve the mechanical strength of concrete. In addition, the present invention prepares a modified recycled micropowder strengthener with the waste slurry produced by the commercial mixing station to produce cement-based slurry, which not only realizes the utilization of this solid waste, but also strengthens the strength of the prepared 3D printed concrete. The present invention combines the waste slurry with γ-C 2 S powder is mixed and carbonized, and the γ-C 2 S has a very low hydration activity, but can react quickly with carbon dioxide, which not only 2The modified regenerated micro-powder fortifier is used to convert the waste slurry into calcium carbonate and nano-silicon dioxide, and the calcium hydroxide in the waste slurry is also converted into calcium carbonate, while the consumption and solidification of carbon dioxide is realized. After the modified regenerated micro-powder fortifier enters the concrete, the nano-silicon dioxide and the calcium hydroxide, a hydration product of cement, undergo a secondary hydration reaction to form a hydrated calcium silicate gelling component, thereby improving the strength of the concrete structure. At the same time, the calcium carbonate also helps to fill the pores in the concrete matrix, improve the density, and help to improve the strength of the concrete structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein: Figure 1 The following is a diagram showing the effect of 3D printing of the low-carbon concrete prepared in Example 1.
[0021] Figure 2 This is a rheological test diagram of the 3D printed low-carbon concrete prepared in the following Example 1. DETAILED DESCRIPTION
[0022] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer. Now the present invention will be further described in conjunction with specific embodiments.
[0023] Example 1 A method for preparing 3D printed low-carbon concrete containing modified recycled aggregate and micro-powder reinforcer comprises the following steps: (1) Add 40 g / L of continuously graded recycled concrete coarse aggregate with a particle size between 10 and 20 mm to 30% sodium water glass by mass, and then treat it with ultrasonic oscillation for 35 minutes. After completion, filter out the coarse aggregate, place it in a high-pressure reactor, seal it, fill it with carbon dioxide gas, set the pressure to 0.3 MPa, and then heat it to 50°C for 1 hour for carbonization treatment. After completion, heat the obtained coarse aggregate at 220°C until the weight is constant to obtain pretreated recycled aggregate.
[0024] (2) Add the pretreated recycled aggregate into saturated lime water at a ratio of 30 g / L, and then heat it in a water bath to 60° C. for 5.5 h. After completion, filter out the solid matter and dry it in the air to obtain the modified recycled aggregate for later use.
[0025] (3) Separate the precipitate from the silicate cement-based waste slurry after settling, dry it, grind it, and sieve it to obtain the powder (fineness 200 mesh), γ-C 2 S powder (fineness 200 mesh) and water are mixed in a ratio of 1.0 weight part: 0.2 weight part: 0.35 weight part and stirred evenly to form a wet material, and then the wet material is placed in a high-pressure reactor, sealed and filled with carbon dioxide gas for carbonization treatment for 40 minutes, and the pressure is set to 0.3MPa. After completion, the obtained product is taken out and heated at 85°C for 2 hours, and the obtained solid is ground and passed through a 500-mesh sieve to obtain a modified regenerated micro-powder strengthener for standby use.
[0026] (4) Take the following components: 330 parts by weight of 42.5 ordinary Portland cement, 670 parts by weight of the modified recycled aggregate of this embodiment, 440 parts by weight of river sand fine aggregate with a particle size between 0.5 and 1 mm, 60 parts by weight of the modified recycled micropowder strengthener of this embodiment, 6.5 parts by weight of polycarboxylic acid water reducer, and 132 parts by weight of clean water. Mix the above components and stir for 3 minutes to obtain 3D printed low-carbon concrete.
[0027] After the 3D printed low-carbon concrete of this embodiment is printed (such as Figure 1 The 3D printed low-carbon concrete was naturally cured for 28 days, and then the specimens were cut out and the compressive strength of the specimens was tested according to the "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GB / T 50081-2019). In addition, the 3D printed low-carbon concrete was subjected to a creep-recovery test using the "HAAKE Mars 40 rotational rheometer" (as shown in the figure). Figure 2 The results show that the compressive strength is 52.39 MPa and the recovery deformation rate is 83.7%.
[0028] Example 2 A method for preparing 3D printed low-carbon concrete containing modified recycled aggregate and micro-powder reinforcer comprises the following steps: (1) Add 25 g / L of continuously graded recycled concrete coarse aggregate with a particle size between 10 and 20 mm to 20% potassium water glass by mass, and then treat it with ultrasonic oscillation for 30 minutes. After completion, filter out the coarse aggregate, place it in a high-pressure reactor, seal it, fill it with carbon dioxide gas, set the pressure to 0.35 MPa, and then heat it to 40°C for 1.5 hours for carbonization treatment. After completion, heat the obtained coarse aggregate at 180°C until the weight is constant to obtain pretreated recycled aggregate.
[0029] (2) Add the pretreated recycled aggregate into saturated lime water at a ratio of 20 g / L, and then heat it in a water bath to 50° C. for 7 hours. After completion, filter out the solid matter and dry it in the air to obtain the modified recycled aggregate for later use.
[0030] (3) Separate the precipitate from the silicate cement-based waste slurry after settling, dry it, grind it, and sieve it to obtain the powder (fineness 300 mesh), γ-C 2 S powder (fineness 300 mesh) and water are mixed in a ratio of 1.15 parts by weight: 0.25 parts by weight: 0.4 parts by weight and stirred evenly to form a wet material, and then the wet material is placed in a high-pressure reactor, sealed and filled with carbon dioxide gas for carbonization treatment for 50 minutes, and the pressure is set to 0.2MPa. After completion, the obtained product is taken out and heated at 100°C for 1 hour, and the obtained solid is ground and passed through a 600-mesh sieve to obtain a modified regenerated micro-powder strengthener for standby use.
[0031] (4) Take the following components: 360 parts by weight of 42.5 ordinary Portland cement, 750 parts by weight of the modified recycled aggregate in this embodiment, 480 parts by weight of river sand fine aggregate with a particle size between 0.5 and 1 mm, 70 parts by weight of the modified recycled micropowder strengthener in this embodiment, 7.2 parts by weight of naphthalene-based water reducer, and 162 parts by weight of clean water. Mix the above components and stir for 3 minutes to obtain 3D printed low-carbon concrete.
[0032] The compressive strength and creep-recovery tests were performed on the 3D printed low-carbon concrete prepared in this embodiment using the same method as in Example 1. The results showed that the compressive strength was 51.83 MPa and the recovery deformation rate was 85.4%.
[0033] Example 3 A method for preparing 3D printed low-carbon concrete containing modified recycled aggregate and micro-powder reinforcer comprises the following steps: (1) Add 70 g / L of continuously graded recycled concrete coarse aggregate with a particle size between 10 and 20 mm to 35% sodium water glass by mass, and then treat it with ultrasonic oscillation for 40 minutes. After completion, filter out the coarse aggregate, place it in a high-pressure reactor, seal it and fill it with carbon dioxide gas, set the pressure to 0.2 MPa, and then heat it to 60°C for 1.5 hours for carbonization treatment. After completion, heat the obtained coarse aggregate at 250°C until the weight is constant to obtain pretreated recycled aggregate.
[0034] (2) Add the pretreated recycled aggregate into saturated lime water at a ratio of 40 g / L, and then heat it in a water bath to 80° C. for 4 h. After completion, filter out the solid matter and dry it in the air to obtain the modified recycled aggregate for later use.
[0035] (3) Separate the precipitate from the silicate cement-based waste slurry after settling, dry it, grind it, and sieve it to obtain the powder (fineness 200 mesh), γ-C 2S powder (fineness 200 mesh) and water are mixed in a ratio of 1.1 parts by weight: 0.18 parts by weight: 0.3 parts by weight and stirred evenly to form a wet material, and then the wet material is placed in a high-pressure reactor, sealed and filled with carbon dioxide gas for carbonization treatment for 30 minutes, and the pressure is set to 0.35MPa. After completion, the obtained product is taken out and heated at 80°C for 1.5 hours, and the obtained solid is ground and passed through a 300-mesh sieve to obtain a modified regenerated micro-powder strengthener for standby use.
[0036] (4) Take the following components: 300 parts by weight of 42.5 ordinary Portland cement, 620 parts by weight of the modified recycled aggregate of this embodiment, 400 parts by weight of river sand fine aggregate with a particle size between 0.5 and 1 mm, 50 parts by weight of the modified recycled micro-powder strengthener of this embodiment, 4.5 parts by weight of sodium lignin sulfonate water reducer, and 105 parts by weight of clean water. Mix the above components and stir for 3 minutes to obtain 3D printed low-carbon concrete.
[0037] The compressive strength and creep-recovery tests were performed on the 3D printed low-carbon concrete prepared in this embodiment using the same method as in Example 1. The results showed that the compressive strength was 54.12 MPa and the recovery deformation rate was 81.6%.
[0038] Example 4 A method for preparing 3D printed low-carbon concrete containing modified recycled aggregate and micro-powder reinforcer comprises the following steps: (1) Add 40 g / L of recycled concrete coarse aggregate with a particle size between 10 and 20 mm and continuously graded into clean water, and then treat it with ultrasonic oscillation for 35 minutes. After completion, filter out the coarse aggregate, place it in a high-pressure reactor, seal it, fill it with carbon dioxide gas, set the pressure to 0.3 MPa, and then heat it to 50°C for 1 hour for carbonization treatment. After completion, heat the obtained coarse aggregate at 220°C until the weight is constant to obtain pretreated recycled aggregate.
[0039] (2) Add the pretreated recycled aggregate into saturated lime water at a ratio of 30 g / L, and then heat it in a water bath to 60° C. for 5.5 h. After completion, filter out the solid matter and dry it in the air to obtain the modified recycled aggregate for later use.
[0040] (3) Take the following components: 330 parts by weight of 42.5 ordinary Portland cement, 670 parts by weight of the modified recycled aggregate of this embodiment, 440 parts by weight of river sand fine aggregate with a particle size between 0.5 and 1 mm, 60 parts by weight of the modified recycled micropowder strengthener prepared in Example 1, 6.5 parts by weight of polycarboxylate water reducer, and 132 parts by weight of clean water. Mix the above components and stir for 3 minutes to obtain 3D printed low-carbon concrete.
[0041] The compressive strength and creep-recovery tests were performed on the 3D printed low-carbon concrete prepared in this embodiment using the same method as in Example 1. The results showed that the compressive strength was 45.27 MPa and the recovery deformation rate was 72.5%.
[0042] Example 5 A method for preparing 3D printed low-carbon concrete containing modified recycled aggregate and micro-powder reinforcer comprises the following steps: (1) Add 70 g / L of continuously graded recycled concrete coarse aggregate with a particle size between 10 and 20 mm to 35% sodium water glass by mass, and then treat it with ultrasonic oscillation for 40 minutes. After completion, filter out the coarse aggregate, place it in a high-pressure reactor, seal it and fill it with carbon dioxide gas, set the pressure to 0.2 MPa, and then heat it to 60°C for 1.5 hours for carbonization treatment. After completion, heat the obtained coarse aggregate at 250°C until the weight is constant to obtain pretreated recycled aggregate.
[0043] (1) Add 70 g / L of continuously graded recycled concrete coarse aggregate with a particle size between 10 and 20 mm to 35% sodium water glass by mass, and then treat it with ultrasonic oscillation for 40 minutes. After completion, filter out the coarse aggregate, place it in a high-pressure reactor, seal it, heat it to 60°C and keep it warm for 1.5 hours, and after completion, heat the obtained coarse aggregate at 250°C until the weight is constant to obtain pretreated recycled aggregate.
[0044] (2) Add the pretreated recycled aggregate into saturated lime water at a ratio of 40 g / L, and then heat it in a water bath to 80° C. for 4 h. After completion, filter out the solid matter and dry it in the air to obtain the modified recycled aggregate for later use.
[0045] (3) Take the following components: 300 parts by weight of 42.5 ordinary Portland cement, 620 parts by weight of the modified recycled aggregate of this embodiment, 400 parts by weight of river sand fine aggregate with a particle size between 0.5 and 1 mm, 50 parts by weight of the modified recycled micropowder strengthener of Example 3, 4.5 parts by weight of sodium lignin sulfonate water reducer, and 105 parts by weight of clean water. Mix the above components and stir for 3 minutes to obtain 3D printed low-carbon concrete.
[0046] The compressive strength and creep-recovery tests were performed on the 3D printed low-carbon concrete prepared in this embodiment using the same method as in Example 1. The results showed that the compressive strength was 49.04 MPa and the recovery deformation rate was 77.1%.
[0047] Example 6 A method for preparing 3D printed low-carbon concrete containing modified recycled aggregate and micro-powder reinforcer comprises the following steps: (1) Add 25 g / L of recycled concrete coarse aggregate with a particle size between 10 and 20 mm to 20% potassium water glass by mass, and then treat it with ultrasonic vibration for 30 minutes. After completion, filter out the coarse aggregate, place it in a high-pressure reactor, seal it, fill it with carbon dioxide gas, set the pressure to 0.35 MPa, and then heat it to 40°C for 1.5 hours for carbonization treatment to obtain pretreated recycled aggregate.
[0048] (2) Add the pretreated recycled aggregate into saturated lime water at a ratio of 20 g / L, and then heat it in a water bath to 50° C. for 7 hours. After completion, filter out the solid matter and dry it in the air to obtain the modified recycled aggregate for later use.
[0049] (3) Take the following components: 360 parts by weight of 42.5 ordinary Portland cement, 750 parts by weight of the modified recycled aggregate of this embodiment, 480 parts by weight of river sand fine aggregate with a particle size between 0.5 and 1 mm, 70 parts by weight of the modified recycled micropowder strengthener of Example 2, 7.2 parts by weight of naphthalene-based water reducer, and 162 parts by weight of clean water. Mix the above components and stir for 3 minutes to obtain 3D printed low-carbon concrete.
[0050] The compressive strength and creep-recovery tests were performed on the 3D printed low-carbon concrete prepared in this embodiment using the same method as in Example 1. The results showed that the compressive strength was 46.71 MPa and the recovery deformation rate was 79.3%.
[0051] Example 7 A method for preparing 3D printed low-carbon concrete containing modified recycled aggregate and micro-powder reinforcer comprises the following steps: (1) After the silicate cement-based waste slurry is precipitated, the precipitate is separated, dried, ground and sieved to obtain a fine powder with a fineness of 200 mesh, which is set aside.
[0052] (2) Take the following components: 330 parts by weight of 42.5 ordinary Portland cement, 670 parts by weight of the modified recycled aggregate of Example 1, 440 parts by weight of river sand fine aggregate with a particle size between 0.5 and 1 mm, 60 parts by weight of the micropowder of this example, 6.5 parts by weight of polycarboxylate water reducer, and 132 parts by weight of clean water. Mix the above components and stir for 3 minutes to obtain 3D printed low-carbon concrete.
[0053] The compressive strength and creep-recovery tests were performed on the 3D printed low-carbon concrete prepared in this embodiment using the same method as in Example 1. The results showed that the compressive strength was 50.16 MPa and the recovery deformation rate was 82.9%.
[0054] Example 8 A method for preparing 3D printed low-carbon concrete containing modified recycled aggregate and micro-powder reinforcer comprises the following steps: (1) After the silicate cement-based waste slurry is precipitated, the precipitate is separated, dried, ground and sieved, and the obtained powder (fineness 300 mesh) is mixed with water in a ratio of 1.15 parts by weight: 0.4 parts by weight and stirred evenly to form a wet material, and then the wet material is placed in a high-pressure reactor, sealed and filled with carbon dioxide gas for carbonization treatment for 50 minutes, and the pressure is set to 0.2MPa. After completion, the obtained product is taken out and heated at 100°C for 1 hour, and the obtained solid is ground and sieved through a 600-mesh sieve to obtain a modified regenerated micropowder strengthener for standby use.
[0055] (2) Take the following components: 360 parts by weight of 42.5 ordinary Portland cement, 750 parts by weight of the modified recycled aggregate of Example 2, 480 parts by weight of river sand fine aggregate with a particle size between 0.5 and 1 mm, 70 parts by weight of the modified recycled micropowder strengthener of this example, 7.2 parts by weight of naphthalene-based water reducer, and 162 parts by weight of clean water. Mix the above components and stir for 3 minutes to obtain 3D printed low-carbon concrete.
[0056] The compressive strength and creep-recovery tests were performed on the 3D printed low-carbon concrete prepared in this embodiment using the same method as in Example 1. The results showed that the compressive strength was 48.43 MPa and the recovery deformation rate was 85.1%.
[0057] Example 9 A method for preparing 3D printed low-carbon concrete containing modified recycled aggregate and micro-powder reinforcer comprises the following steps: (1) The silicate cement-based waste slurry is precipitated and the precipitate is separated, which is then dried and ground and sieved to obtain a powder (fineness 200 mesh), γ-C 2 S powder (fineness 200 mesh) and water are mixed in a ratio of 1.1 parts by weight: 0.18 parts by weight: 0.3 parts by weight and stirred evenly to form a wet material, which is heated at 80°C for 1.5 hours. The obtained solid is ground and passed through a 300-mesh sieve to obtain a modified regenerated micropowder fortifier, which is set aside.
[0058] (2) Take the following components: 300 parts by weight of 42.5 ordinary Portland cement, 620 parts by weight of the modified recycled aggregate in Example 3, 400 parts by weight of river sand fine aggregate with a particle size between 0.5 and 1 mm, 50 parts by weight of the modified recycled micropowder strengthener in this example, 4.5 parts by weight of sodium lignin sulfonate water reducer, and 105 parts by weight of clean water. Mix the above components and stir for 3 minutes to obtain 3D printed low-carbon concrete.
[0059] The compressive strength and creep-recovery tests were performed on the 3D printed low-carbon concrete prepared in this embodiment using the same method as in Example 1. The results showed that the compressive strength was 49.56 MPa and the recovery deformation rate was 80.8%.
[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A 3D printed low-carbon concrete containing modified recycled aggregate and micro-powder reinforcer, characterized in that: The composition includes: 300-360 parts by weight of cementitious material, 620-750 parts by weight of modified recycled aggregate, 400-480 parts by weight of fine aggregate, 50-70 parts by weight of modified recycled micro powder strengthening agent, 4.5-7.2 parts by weight of water reducing agent, clean water, and the water-cement ratio is 0.35-0.45; wherein: The modified recycled aggregate and modified recycled micropowder strengthening agent are prepared by the following method: (1) placing recycled concrete coarse aggregate in sodium or potassium water glass and then subjecting it to ultrasonic treatment; then separating the coarse aggregate and subjecting it to carbonization treatment in a closed container with a carbon dioxide atmosphere, and after completion, heating the obtained coarse aggregate to obtain pretreated recycled aggregate; (2) placing the pretreated recycled aggregate in saturated lime water and performing a heating and heat preservation treatment, and separating the solid matter after completion to obtain the modified recycled aggregate; (3) After the silicate cement-based waste slurry is precipitated, the precipitate is separated, the precipitate is dried and then ground into powder, the powder, γ-C2S powder and water are evenly mixed to form a wet material, and the wet material is placed in a closed container with a carbon dioxide atmosphere for carbonization treatment. After completion, it is heated and the obtained solid matter is ground to obtain the modified regenerated micropowder strengthener.
2. The 3D printed low-carbon concrete containing modified recycled aggregate and micro-powder reinforcer according to claim 1, characterized in that: In step (1), the amount of recycled concrete coarse aggregate added to the sodium or potassium water glass is 25-70 g / L; Optionally, in step (1), the mass fraction of the sodium or potassium water glass is not less than 20%.
3. The 3D printed low-carbon concrete containing modified recycled aggregate and micro-powder reinforcer according to claim 1, characterized in that: In step (1), the ultrasonic treatment time is 30 to 40 minutes; Optionally, in step (1), the particle size of the recycled concrete coarse aggregate is 10-20 mm.
4. The 3D printed low-carbon concrete containing modified recycled aggregate and micro-powder reinforcer according to claim 1, characterized in that: In step (1), the carbonization treatment temperature is 40-60°C and the time is 1-1.5h; Optionally, in step (1), the pressure in the sealed container is 0.2-0.35 MPa.
5. The 3D printed low-carbon concrete containing modified recycled aggregate and micro-powder reinforcer according to claim 1, characterized in that: In step (1), the heating treatment temperature is 180-250° C., and the heating treatment is performed at this temperature until the weight of the coarse aggregate becomes constant.
6. The 3D printed low-carbon concrete containing modified recycled aggregate and micro-powder reinforcer according to claim 1, characterized in that: In step (2), the amount of pre-treated recycled aggregate added to the saturated lime water is 20-40 g / L.
7. The 3D printed low-carbon concrete containing modified recycled aggregate and micro-powder reinforcer according to claim 1, characterized in that: In step (2), the heating temperature is 50-80° C. and the heating time is 4-7 hours.
8. The 3D printed low-carbon concrete containing modified recycled aggregate and micro-powder reinforcer according to claim 1, characterized in that: In step (3), the ratio of the powder, γ-C2S powder and water is 1-1.15 parts by weight: 0.18-0.25 parts by weight: 0.3-0.4 parts by weight; Optionally, in step (3), the fineness of the powder and γ-C2S powder is not less than 200 mesh.
9. The 3D printed low-carbon concrete containing modified recycled aggregate and micro-powder reinforcer according to claim 1, characterized in that: In step (3), the carbonization treatment time is 30 to 50 minutes; Optionally, in step (3), the pressure in the sealed container is 0.2-0.35 MPa; Optionally, in step (3), the heating treatment temperature is 80-100°C and the time is 1-2h; Optionally, in step (3), the modified regenerated micropowder fortifier has a fineness of 300-600 mesh.
10. The 3D printed low-carbon concrete containing modified recycled aggregate and micro-powder reinforcer according to any one of claims 1 to 9, characterized in that: The water reducer includes any one of a polycarboxylate water reducer, a lignin sulfonate water reducer, a naphthalene water reducer, and an aliphatic water reducer; Optionally, the particle size of the fine aggregate is 0.5-1 mm; Optionally, the fine aggregate includes at least one of river sand and machine-made sand.
Citation Information
Patent Citations
3D printing concrete material containing coarse aggregate and manufacturing method of 3D printing concrete material
CN114163183A
3D printing concrete with adjustable rheological property, preparation method and printing process
CN114804791A
Multi-layer composite base material capable of improving carbonization degree and preparation method of multi-layer composite base material
CN115504715A
Self-compacting durable concrete and preparation method thereof
CN116768548A
Regenerated micro-powder green admixture as well as preparation method and application thereof
CN118047553A
Cited By
Preparation method and application of steel slag aggregate carbon sequestration marine concrete material
CN121494373A
Device and method for testing ultra-early creep deformation of 3D printing concrete
CN121521596A
Preparation method of early-strength carbon-reduction lightweight aggregate cement-based material
CN121698611A